2003
DOI: 10.2527/2003.81112869x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between bunk management and monensin concentration on finishing performance, feeding behavior, and ruminal metabolism during an acidosis challenge with feedlot cattle1

Abstract: Two commercial feedlot experiments and a metabolism study were conducted to evaluate the effects of monensin concentrations and bunk management strategies on performance, feed intake, and ruminal metabolism. In the feedlot experiments, 1,793 and 1,615 steers were used in Exp. 1 and 2, respectively, in 18 pens for each experiment (six pens/treatment). Three treatments were evaluated: 1) ad libitum bunk management with 28.6 mg/kg monensin and clean bunk management strategies with either 2) 28.6 or 3) 36.3 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 14 publications
5
43
2
5
Order By: Relevance
“…Our results for total daily meal-time, meal frequency and eating rate are similar to those reported in a series of experiments working with steers by Putnam and Davis (1963) who fed 24% ground forage (15-min meal criterion), and Chase et al (1976) who fed 28% chopped hay (20-min meal criterion). However, other researchers have reported a much higher daily meal-time, size and length than the present trial when working with steers fed around 10% forage in diets and when using a 20-min meal criterion (Cooper et al, 1999;Erickson et al, 2003). Results are difficult to compare because of different experimental conditions and the selection of the meal criterion may affect the estimation of all these variables (Tolkamp and Kyriazakis, 1999).…”
Section: Discussioncontrasting
confidence: 71%
“…Our results for total daily meal-time, meal frequency and eating rate are similar to those reported in a series of experiments working with steers by Putnam and Davis (1963) who fed 24% ground forage (15-min meal criterion), and Chase et al (1976) who fed 28% chopped hay (20-min meal criterion). However, other researchers have reported a much higher daily meal-time, size and length than the present trial when working with steers fed around 10% forage in diets and when using a 20-min meal criterion (Cooper et al, 1999;Erickson et al, 2003). Results are difficult to compare because of different experimental conditions and the selection of the meal criterion may affect the estimation of all these variables (Tolkamp and Kyriazakis, 1999).…”
Section: Discussioncontrasting
confidence: 71%
“…However, with G diets, LC reduced (2.1%; P 00.03) the frequency of daily visits (9.3 vs. 9.5), but increased (6%; P B0.001) the duration at the bunk (135.9 vs. 124.0; interaction P B0.001), resulting in increased (12.4%; P B0.001) duration per meal (15.4 vs. 13.7 min). Increased frequency of meals has previously been observed in cattle supplemented with monensin compared with control (Laudert 1995;Erickson et al 2003) or cattle fed salinomycin (Gibb et al 2001). The reduced intakes often observed with feeding monensin are typically associated with more frequent, but smaller meals, resulting in more stable intakes (Chirase et al 1992;Laudert 1995;Gibb et al 2001).…”
Section: Bunk Attendancementioning
confidence: 94%
“…The second stepwise regression indicated that liver abscesses also increased with increasing frequency of bunk visits (P 00.002; R 2 00.16). Acidosis reduces DMI (Fulton et al 1979;Erickson et al 2003) and contributes to liver abscesses (Galyean and Rivera 2003), both of which can reduce performance (Brink et al 1990). It is possible that the acidosis challenges that resulted in abscessed livers also altered eating patterns, resulting in more frequent visits to the bunk.…”
Section: Bunk Attendancementioning
confidence: 99%
See 1 more Smart Citation
“…46 A carboxylic polyether ionophore widely used as a feed additive in beef cattle, monensin functions as described above in addition to its use for prevention and control of coccidiosis in cattle. 47 In 2004, the FDA approved use of monensin in total mixed rations for increased milk production efficiency in dairy cattle; the following year, ionophores were widely approved for use in dairy cattle. 48 Intoxications occur as a result of error in the amount of ionophore added to the diet, 49 inaccurate on-farm feeding, 50 administration to the wrong cohort, or exposure of cattle not acclimated to the ionophore-containing ration.…”
Section: Feed-related Toxicantsmentioning
confidence: 99%